Different Enzyme Conformations Induce Different Mechanistic Traits in HIV‐1 Protease. Issue 42 (27th June 2022) - Coimbra, João T. S.; Neves, Rui P. P.; Cunha, Ana V.; Ramos, Maria J.; Fernandes, Pedro A.
Abstract: The influence of the dynamical flexibility of enzymes on reaction mechanisms is a cornerstone in biological sciences. In this study, we aim to 1) study the convergence of the activation free energy by using the first step of the reaction catalysed by HIV‐1 protease as a case study, and 2) provide further evidence for a mechanistic divergence in this enzyme, as two different reaction pathways were seen to contribute to this step. We used quantum mechanics/molecular mechanics molecular dynamics simulations, on four different initial conformations that led to different barriers in a previous study. Despite the sampling, the four activation free energies still spanned a range of 5.0 kcal ⋅ mol −1 . Furthermore, the new simulations did confirm the occurrence of an unusual mechanistic divergence, with two different mechanistic pathways displaying equivalent barriers. An active‐site water molecule is proposed to influence the mechanistic pathway. Abstract : Convergence and divergence : Using multiple conformations (previously characterized by adiabatic methods) and quantum mechanics/molecular mechanics molecular dynamics simulations, we assessed the convergence of activation free energies and the mechanistic divergence of the first step in the reaction catalysed by HIV‐1 protease. The mechanistic divergence for this step was still present and our barriers spanned a range of 5 kcal ⋅ mol −1 .